TGFβ1, TGFβ2, and TGFβ3 Protein Expression in Gastric Carcinomas: Correlation with Prognostics Factors and Patient Survival - Vagenas, Konstantinos; Spyropoulos, Charalambos; Gavala, Vasiliki; Tsamandas, Athanassios C. (The Journal of surgical research, 2007)
This study evaluates the expression of transforming growth factors TGFβ1, TGFβ2 and TGFβ3 in cases of gastric carcinoma and their possible correlation with classic prognostic markers and patient survival. The study included 110 gastrectomy specimens obtained from equal number of patients with gastric cancer. According to the TNM classification, 7 tumors were identified as being stage I, 33 stage II, 52 stage III, and 18 stage IV, whereas 92 tumors were low-grade and 18 high-grade malignancies. On paraffin sections, the streptavidin-biotin technique using antibodies against TGFβ1, TGFβ2, and TGFβ3 was applied. Morphological and immunohistochemical results were correlated with clinicopathologic parameters. TGFβ1 was expressed in 78 out of 110 (71%) carcinomas, whereas TGFβ2 and TGFβ3 were detected in all tumors examined. Normal gastric mucosal epithelial cells expressed TGFβ2 and TGFβ3, but not TGFβ1. Statistical analysis revealed higher expression of TGFβ1 in low grade carcinomas ( P = 0.009). TGFβ2 presence was higher in advanced stage tumors ( P = 0.008) and was correlated with worse prognosis ( P < 0.05). TGFβ1 expression was related to increased disease-free survival ( P < 0.05) while Cox analysis revealed that TGFβ1 expression constituted an independent prognostic factor. Gastric carcinoma is related to differential expression of TGFβ1, TGFβ2, and TGFβ3. TGFβ1 may be implicated in the pathogenesis of the tumors, since it is expressed only in neoplastic tissue. TGFβ1 is related with an increased disease-free and overall survival constituting an independent prognostic factor. In advanced stages, TGFβ2 seems to be involved in tumor progression related to worse prognosis.